Computer Analysis of Images and Patterns 16th International Conference, CAIP 2015, Valletta, Malta, September 2-4, 2015 Proceedings, Part I - Azzopardi, George; Petkov, Nicolai (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2015)
The two volume set LNCS 9256 and 9257 constitutes the refereed proceedings of the 16th International Conference on Computer Analysis of Images and Patterns, CAIP 2015, held in Valletta, Malta, in September 2015. The 138 papers presented were carefully reviewed and selected from numerous submissions. CAIP 2015 is the sixteenth in the CAIP series of biennial international conferences devoted to all aspects of computer vision, image analysis and processing, pattern recognition, and related fields.